Intestinal pseudo-obstruction in a patient with Kleefstra syndrome : a case report = Intestinalna pseudoopstrukcija u pacijenta sa sindromom Kleefstra : prikaz slučaja - Golem, Nikolina (Array, 2021)
Aim: To present a case of intestinal pseudo-obstruction in a paediatric patient with Kleefstra syndrome type 1 as a new clinical feature of this rare genetic disorder. Case report: A seven-year-old patient was admitted to the emergency department for nausea and vomiting. Clinical examination showed distended, meteoristic abdomen without detectable peristaltic sound. Abdominal X-ray revealed air-fluid levels and possible right subdiaphragmatic air collection. An urgent exploratory laparotomy was indicated. Intraoperatively, extremely dilated loops of small and large intestine up to the distal sigmoid colon were noted. No anatomical or mechanical causes of obstruction were found. The postoperative course was complicated by dysfunctional intestinal motility and urinary catheter-related infection which required prokinetics and intravenous antibiotic therapy. The patient was transferred to a paediatric centre specialized in intestinal motility disorders for further treatment. Conclusion: This is the first case of intestinal pseudo-obstruction described as a part of clinical presentation of Kleefstra syndrome type 1. Further research and re-evaluation of patients with KS1 is needed to determine if intestinal pseudo-obstruction is a new clinical manifestation depending on the size of the deletion or a repercussion of hypotonia sequential to an underlying syndrome.